Synthesis of novel quaternary ammonium salts from 1, 2-benzothiazine derivatives. (2nd January 2021) - Gul, Salman; Saleem, Maria; Munawar, Munawar Ali; Ahmad, Hafiz Adnan; Ahmed, Ejaz; Begum, Robina; Farooqi, Zahoor H.
Abstract : A series of novel 1, 2-benzothiazine based quaternary ammonium salts were successfully prepared through different organic transformations. Products of all transformations and final salts were separated out and purified. The product yields were good to excellent for all transformations. Resultant 1, 2-benzothiazine based cationic amphiphilic systems were stabilized using different counter anions. All final products were confirmed by 1 HNMR and 13 CNMR analyses. 1, 2-benzothiazine based quaternary ammonium salts have a potential to be employed as a phase transfer catalyst for various reactions in future. GRAPHICAL ABSTRACT: